Development of traffic light control system using programmable logic controller - Ahmad, Azrulnor (2007)
Development of a traffic light control system using PLC (Programmable Logic Controller) is the title of this project. This project is divided into two parts which are hardware and software. The hardware part for this project is a model of four way junction of a traffic light. Each lane has two limits switch (input) function as a sensor. Three indicator lamps with different colours (Red, Yellow and Green) are installed at each lane for represents as traffic light signal. This limit switches and indicator lamps are connected to Omron PLC CQM1H-CPU51. The PLC controls every signal which is coming from the inputs (Limit switch) to software and display to the outputs (Indicator lamps). The software part operates with Omron PLC is CX-Programmer. With using this software, the ladder logic diagram is programmed to control the traffic light base on the flow chart. At the end of this project, the traffic light successfully control by PLC.